The impact of world evaluation standards on assessment of agricultural property in Ukraine - Avramchuk, B. (Land Management, Cadastre and Land Monitoring, 2017)
Analyzed the basic principles of the assessment of agricultural property within the major world evaluation standards and their impact on evaluation standards in Ukraine.. Keywords: real estate, property, agriculture, property appraisal, assessment standards.